Out of stoichiometry CuCrO2 films as a promising p-type TCO for transparent electronics. Issue 14 (18th June 2021) - Bottiglieri, Lorenzo; Resende, João; Weber, Matthieu; Chaix-Pluchery, Odette; Jiménez, Carmen; Deschanvres, Jean-Luc
Abstract : Optimal deposition conditions to synthesize highly conductive and transparent CuCrO2 films out of stoichiometry and Cu2 O + CuCrO2 nanocomposite films by AA-MOCVD at a low temperature and atmospheric pressure. Abstract : In this work, we report the enhancement of the functional properties of CuCrO2, a promising p-type transparent conductive oxide, achieved in out of stoichiometry CuCrO2 thin films synthesized by aerosol-assisted chemical vapor deposition. Out of stoichiometry films consisting of Cr-deficient CuCrO2, i.e. Cu-rich CuCrO2 phase, have a resistivity value of 0.05 Ω cm and an average transmittance of 58% in the visible range, resulting in a Gordon's figure of merit of 2200 μS. This is the highest ever published figure of merit among Cu-rich CuCrO2 films synthesized by chemical methods. A remarkable result is that when further increasing the Cu/(Cu + Cr) ratio, the formation of CuO was not detected, allowing the synthesis of composite films formed by Cu2 O and CuCrO2 p-type oxides, which are more conductive than the Cu-rich CuCrO2 phase. These nanocomposite films present an improved carrier mobility, with a resistivity value of around 0.02 Ω cm, and a reduced energy gap, with a transmittance of 52%, resulting in a figure of merit of 1400 μS. Both these thin films can find applications as a hole transport layer in various transparent optoelectronic devices where p-type TCOs are required, especially when synthesized by a solution-based process at a low temperature and ambient pressure over large surface areas.